The host : a novel - Meyer, Stephenie, 1973- (New York : Little, Brown, 2011)
Melanie, whose mind has been almost completely taken over by an alien named Wanderer, convinces the alien to search for her lost lover, who fled the extraterrestrial invasion, and tries to find a way in which she and Wanderer can coexist.
Library Journal Starred
School Library Journal
Wilson's Fiction
Booklist, March 2008
Library Journal Starred, April 2008
Publisher's Weekly, March 2008
Keywords: Spirit possession -- Fiction; Love stories; Science fiction; Spirits -- Fiction; Love stories; Science fiction